A Case of Parathyroid Carcinoma Visualized on Tc-99m-Sestamibi Scintigraphy - Aigner, Reingard M.; Fueger, G. F.; Lax, S. (Nuklearmedizin - NuclearMedicine, 1997)
Recent studies indicate that Tc-99m-Sestamibi (MIBI, DuPont Pharma) is a useful tracer for detecting parathyroid adenomas. We present a patient with focal Tc-99m-MIBI uptake in parathyroid carcinoma which has only been described once before (1). Tc-99m-MIBI scintigraphy may be considered for diagnosing pathological parathyroid tissue. But presently the histopathological examination only allows the differentiation between adenoma and carcinoma.
Keywords: Tc-99m-Sestamibi; parathyroid carcinoma; parathyroid adenoma